Does Osmotic Stress Affect Natural Product Expression in Fungi? - David Overy; Hebelin Correa; Catherine Roullier; Wei-Chiung Chi; Ka-Lai Pang; Mostafa Rateb; Rainer Ebel; Zhuo Shang; Rob Capon; Gerald Bills; Russell Kerr (Marine Drugs, 2017)
The discovery of new natural products from fungi isolated from the marine environment has increased dramatically over the last few decades, leading to the identification of over 1000 new metabolites. However, most of the reported marine-derived species appear to be terrestrial in origin yet at the same time, facultatively halo- or osmotolerant. An unanswered question regarding the apparent chemical productivity of marine-derived fungi is whether the common practice of fermenting strains in seawater contributes to enhanced secondary metabolism? To answer this question, a terrestrial isolate of Aspergillus aculeatus was fermented in osmotic and saline stress conditions in parallel across multiple sites. The ex-type strain of A. aculeatus was obtained from three different culture collections. Site-to-site variations in metabolite expression were observed, suggesting that subculturing of the same strain and subtle variations in experimental protocols can have pronounced effects upon metabolite expression. Replicated experiments at individual sites indicated that secondary metabolite production was divergent between osmotic and saline treatments. Titers of some metabolites increased or decreased in response to increasing osmolite (salt or glycerol) concentrations. Furthermore, in some cases, the expression of some secondary metabolites in relation to osmotic and saline stress was attributed to specific sources of the ex-type strains.